Measures in Slovenian cattle production at integration into the European Union - Čepin, Slavko; Čepon, Marko; Osterc, Jože; Žgur, Silvester (Acta Agraria Kaposváriensis, 1999)
The paper deals with the role and economic status of cattle production in Slovenian agriculture. The number of cattle and cows for market milk production decreased by 23% and 24.3% during the last twelve years. Nevertheless, in the same period milk production increased nearly by 8%. The purchase of milk per cow increased by more than a half. One of the most important measures for adjustment to the European Union are such conditions that the number of cattle could increase to 500,000 and of cows to 200,000. Number of stickler cows and at the same time beef production should be stimulated by payments.